KUDUMBASHREE PROJECT EMPOWERING WOMEN IN KERALA - Seleena M. and. T. Lysammal
In 1998 – the government of Kerala launched the Kudumbashree project with the aim to eradicate poverty through women empowerment. It focused on improving the income of poor under the leadership of Local Self Governments – formed and empowered by the 73 rd and 74 th Amendments of the constitution of India. Kudumbashree works through many small communities of Self Help Groups (SHG) of Women in Kerala. The strategy has been recognised as effective in bringing the women in rural as well as urban areas together from all spheres of life to fight for their rights and empowerment. Kudumbashree differs from conventional programmes in that it perceives poverty not just as the deprivation of money, but also as the deprivation of basic rights. Women – through the Kudumbashree project – has harnessed the confidence to take claim of their basic rights. The collective voice the Kudumbashree platform has given them has helped them in doing so.